PROMOTING CREATIVITY AND INNOVATION IN THE TEACHING AND LEARNING PROCESS - Karol Anaktototy (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
Creativity and innovation have become cutting-edge technology that was significantly important in today’s technological advancement society. As education has become more advance, the implementation of creativity and innovation in the teaching and learning process was crucial to shaping the creative and innovative young generation for future development. This article was a literature review about the importance of creativity and innovation during the teaching and learning process. This research aimed to deliver creativity and innovation in education by promoting alternatives of activities that benefited not only the schools but also the educational institutions. Creating an environment that enables the school to promote creativity and innovation would bring the advantage for the students to prepare themselves for the future challenge and demands of society to improve their problem-solving skills and unlock their potential for the benefit of their future careers.